LA OPOSICIÓN ESTÁ VIVA... - Baldares Phillips, Eduardo (2000)
To many people in Latin America, the fall of the Soviet Union represented the death of socialism as a political alternative. The capitalist counterpart took control of the continental leadership without taking away the New World of the social contradiction of Third World. Then, the socialist flag waves again with a new comtemporary feeling. The new left wing is on stage. The capitalism changes too.